P662 Pre-treatment vitamin D concentrations do not predict therapeutic outcome to anti-TNF therapies in biologic-naïve patients with active luminal Crohn's disease. (30th January 2023) - Lin, S; Chanchlani, N; Smith, R; Roberts, C; Nice, R; McDonald, T J; Hamilton, B; Bewshea, C; Kennedy, N A; Goodhand, J R; Ahmad, T
Abstract: Background: Vitamin D has a regulatory role in innate and adaptive immune processes. Previous small studies have reported that low pre-treatment vitamin D concentrations are associated with primary non-response and shorter drug persistence to anti-TNF therapy. We sought to assess whether pre-treatment 25-hydroxyvitamin D concentrations predicted primary non-response and non-remission to infliximab and adalimumab in patients with Crohn's disease recruited to the PANTS (Personalised Anti-TNF Therapy in Crohn's disease) study. Methods: We used composite endpoints using the Harvey Bradshaw Index (HBI) in adults and the short paediatric Crohn's disease activity index (sPCDAI) in children, corticosteroid use, and C-reactive protein (CRP) to define primary non-response (Figure 1). Remission was defined as CRP of ≤3 mg/L and HBI of ≤4 points (short paediatric Crohn's disease activity index ≤15 in children), without corticosteroid therapy or exit for treatment failure. 25-hydroxyvitamin D concentrations were measured in stored baseline serum samples and cut-offs for vitamin D status were: deficiency < 25nmol/L, insufficiency 25-50nmol/L and adequacy/sufficiency > 50nmol/L. Results: Samples from 659/898 infliximab (526 Remicade; 133 biosimilar CT-P13) and 448/605 adalimumab (448 Humira) treated patients included in the effectiveness analysis of the PANTS study were included. Overall, 17.1% (189/1107; 95% confidence interval [CI] 15.0 - 19.4%) and 47.7% (528/1107; 95% CI 44.8 - 50.6%) patients had vitamin D deficiency and insufficiency, respectively. At baseline, 22.2% (246/1107) patients were receiving some form of vitamin D supplementation. Multivariable linear regression analysis confirmed that baseline sampling during non-summer months (Figure 2), South Asian ethnicity, lower serum albumin concentrations, higher HBI and nontreatment with vitamin D supplements were independently associated with lower vitamin D concentrations (Figure 3). Primary non-response at week 14 and non-remission at week 54 occurred in 19.3% (116/600; 95% CI 16.4 - 22.7%) and 58.8% (351/597; 95% CI 54.8- 62.7%) patients treated with infliximab and 25.3% (100/396; 95% CI 21.2- 29.8%) and 65.3% (246/377; 95% CI 60.3- 69.9%) of patients treated with adalimumab, respectively. Pre-treatment vitamin D status did not predict response or remission status to anti-TNF therapy at week 14 (infliximab Ppnr = 0.87, adalimumab Ppnr = 0.18) or non-remission at week 54 (infliximab P = 0.12, adalimumab P = 0.59) (Figure 4). Conclusion: Vitamin D deficiency is common in patients with active Crohn's disease. Unlike previous studies, pre-treatment serum 25-hydroxyvitamin D concentration did not predict primary non-response to anti-TNF treatment at week 14 or non-remission at week 54.